Ecological filtering of root microbiomes in oil palm reveals trait-guided targets for bioinoculant design - Li Sim Ho; Joyce Yoon Mei Ding; Noor Azizah Musa; Julia Ibrahim; Geok Yuan Annie Tan; Chee-Keng Teh (Rhizosphere, 2026)

Integrative multi-omics and biochemical validation reveal phenol-to-polyhydroxybutyrate conversion in a palm oil mill effluent microbiome - Izzati Sabri; Siti Suhailah Sharuddin; Mohd Zulkhairi Mohd Yusoff; Nor Azlan Nor Muhammad; Li Sim Ho; Toshinari Maeda; Norhayati Ramli (Journal of Water Process Engineering, 2026)

Distinct roles of SOX9 in self-renewal of progenitors and mesenchymal transition of the endothelium - Jilai Zhao; Laura Sormani; Sebastien Jacquelin; Haiming Li; Cassandra Styke; Chenhao Zhou; Jonathan Beesley; Linus Oon; Simranpreet Kaur; Seen-Ling Sim; Ho Yi Wong; James Dight; et al. (Angiogenesis, 2024)
Regenerative capabilities of the endothelium rely on vessel-resident progenitors termed endothelial colony forming cells (ECFCs). This study aimed to investigate if these progenitors are impacted by conditions (i.e., obesity or atherosclerosis) characterized by increased serum levels of oxidized low-density lipoprotein (oxLDL), a known inducer of Endothelial-to-Mesenchymal Transition (EndMT). Our investigation focused on understanding the effects of EndMT on the self-renewal capabilities of progenitors and the associated molecular alterations. In the presence of oxLDL, ECFCs displayed classical features of EndMT, through reduced endothelial gene and protein expression, function as well as increased mesenchymal genes, contractility, and motility. Additionally, ECFCs displayed a dramatic loss in self-renewal capacity in the presence of oxLDL. RNA-sequencing analysis of ECFCs exposed to oxLDL validated gene expression changes suggesting EndMT and identified SOX9 as one of the highly differentially expressed genes. ATAC sequencing analysis identified SOX9 binding sites associated with regions of dynamic chromosome accessibility resulting from oxLDL exposure, further pointing to its importance. EndMT phenotype and gene expression changes induced by oxLDL in vitro or high fat diet (HFD) in vivo were reversed by the silencing of SOX9 in ECFCs or the endothelial-specific conditional knockout of Sox9 in murine models. Overall, our findings support that EndMT affects vessel-resident endothelial progenitor’s self-renewal. SOX9 activation is an early transcriptional event that drives the mesenchymal transition of endothelial progenitor cells. The identification of the molecular network driving EndMT in vessel-resident endothelial progenitors presents a new avenue in understanding and preventing a range of condition where this process is involved.